1996
DOI: 10.1006/qres.1996.0059
|View full text |Cite
|
Sign up to set email alerts
|

Size Variation in the Rock Hyrax (Procavia capensis) and Late Quaternary Climatic Change in South Africa

Abstract: The average adult size of the rock hyrax varies greatly across South Africa. Regression analysis suggests that mean hyrax size is more closely linked to precipitation than to temperature, probably because precipitation has a much greater impact on preferred hyrax food plants. The relationship between mean size and precipitation is curvilinear, such that size increases up to about 700 mm/annum and declines thereafter. This parallels a tendency for less palatable grasses to replace more palatable ones where rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 40 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The rock hyrax, Procavia capensis, is a member of the Procaviidae family, which is the only living family within the Hyracoidea order (Klein and Cruz-Uribe, 1996). The family consists of three genera: Procavia (the rock hyrax, one species), Heterohyrax (two species) and Dendrohyrax (three species) (Skinner and Chimimba, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The rock hyrax, Procavia capensis, is a member of the Procaviidae family, which is the only living family within the Hyracoidea order (Klein and Cruz-Uribe, 1996). The family consists of three genera: Procavia (the rock hyrax, one species), Heterohyrax (two species) and Dendrohyrax (three species) (Skinner and Chimimba, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The collection of Procavia capensis identified by us, contains 74 bones and teeth from Layers F ( n = 4), E1 ( n = 29), D2 ( n = 10), and also numerous specimens unassigned to layers ( n = 31). Hyrax body‐size gradients follow Bergmann's rule and have been used to track climatic changes in the Pleistocene record (Klein and Cruz‐Uribe 1996). A comparison of tooth measurements from OQ (SI1) with recent and Pleistocene measurements (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is to prevent the handful of very well-sampled localities (e.g., Lake Naivasha, Mount Kenya) from disproportionately influencing the results. Because previous studies have demonstrated that size-climate relationships Faith et al 12 can be linear (Klein, 1986) or quadratic (Klein and Cruz-Uribe, 1996), both leastsquares linear and quadratic regressions are used here. For those size clines that are statistically significant, we conducted a breakpoint analysis using the maximum likelihood approach in the R package 'segmented' (see Muggeo, 2008) to identify possible changes in slope (i.e., breakpoints) indicative of environmental thresholds above or below which a size-cline is observed.…”
Section: Methodsmentioning
confidence: 99%
“…The best known of these relationships is Bergmann's Rule, which (broadly defined) proposes that populations living in cooler climates are larger than their conspecifics in warmer climates (Meiri and Dayan, 2003). Such relationships have long been studied by paleoecologists to reconstruct paleoclimate change in southern Africa from body size shifts of fossil carnivores and various small mammals (Avery, 1982(Avery, , 2004Klein, 1986Klein, , 1991Klein and Cruz-Uribe, 1996). Parallel research in East Africa is lacking, although Marean et al (1994) document potentially climate-mediated size shifts in the mandibular alveolar lengths of Holocene T. splendens from Enkapune ya Muto in Kenya's Central Rift Valley.…”
Section: Introductionmentioning
confidence: 99%